Artifacts of the Encounter: Collective Creation Through Movement and Its Potential to Review Discourses - Velarde Chainskaia, Cristina Natali (2025)
The purpose of this article is to reflect, from a relational perspective, about the creative spaces that arise from the body and movement in the performing arts. Drawing on the experiences of El presidente más feliz and Artilugios de la mirada, we examine how the emergence of ideas and emotions, both singular and collective, in the encounter with others through movement generates a framework that imbues the work with meaning. The relational theory allows us to identify the representational and presentational dimensions that participate in the encounter, inviting us to discuss how these collective spaces in the performing arts, where meanings are constructed collaboratively, can serve as platforms for an ethical-political reflection-action by fostering the coexistence of diverse perspectives on reality.